Autophagy in stem cells - Guan, Jun-Lin (Landes Bioscience, 2013)
Autophagy is a highly conserved cellular process by which cytoplasmic components are sequestered in autophagosomes and delivered to lysosomes for degradation. As a major intracellular degradation and recycling pathway, autophagy is crucial for maintaining cellular homeostasis as well as remodeling during normal development, and dysfunctions in autophagy have been associated with a variety of pathologies including cancer, inflammatory bowel disease and neurodegenerative disease. Stem cells are unique in their ability to self-renew and differentiate into various cells in the body, which are important in development, tissue renewal and a range of disease processes. Therefore, it is predicted that autophagy would be crucial for the quality control mechanisms and maintenance of cellular homeostasis in various stem cells given their relatively long life in the organisms. In contrast to the extensive body of knowledge available for somatic cells, the role of autophagy in the maintenance and function of stem cells is only beginning to be revealed as a result of recent studies. Here we provide a comprehensive review of the current understanding of the mechanisms and regulation of autophagy in embryonic stem cells, several tissue stem cells (particularly hematopoietic stem cells), as well as a number of cancer stem cells. We discuss how recent studies of different knockout mice models have defined the roles of various autophagy genes and related pathways in the regulation of the maintenance, expansion and differentiation of various stem cells. We also highlight the many unanswered questions that will help to drive further research at the intersection of autophagy and stem cell biology in the near future.